PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL) DAN RETURN ON ASSETS (ROA) TERHADAP PERTUMBUHAN KREDIT PADA BANK PEMBANGUNAN DAERAH - Didin Rasyiddin Wahyu; Putra Rahmatullah; Mamay Komarudin; Wahyu Widodo (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
The purpose of the study is to determine whether CAR, NPL and ROA affect Credit Growth at Regional Development Banks listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. This research method uses quantitative research methods, the population in this study is all BPD banks totaling 28 banks and the sample used is 6 BPD banks using saturated samples or saturation sampling, data collection techniques using secondary data, data analysis techniques used in this study consist of statistical descriptions, classical assumption tests, multiple linear regression analysis,  coefficient of determination and statistical hypothesis. Based on  the results of the study, it is known that the CAR tcount is 2,472 > ttable 1,923 and the t-test sig is 0.002 < 0.05, the NPL tcount value is .326 < ttable 1,923 and the t-test sig is 0.747 > 0.05, the ROA t-count value is 2,519 > ttable 1,923 and the t-test sig is 0.001 < 0.05 And the F test results (simultaneous) are obtained Fcalculate is 7,442 > 3.33 Ftable and the F test sig value is 0.001 < 0.05. Thus it can be concluded that partially CAR has a positive effect on Credit Growth, NPL has a negative effect on Credit Growth and ROA has a positive effect on Credit Growth while simultaneously CAR, NPL and ROA affect Credit Growth at BPD Banks listed on the Indonesia Stock Exchange for the 2018-2022 period